1984
DOI: 10.1042/bj2200447
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and e.p.r. studies of cyanide and azide binding to the copper sites of dopamine (3,4-dihydroxyphenethylamine) β-mono-oxygenase

Abstract: The kinetics of inhibition of dopamine (3,4-dihydroxyphenethylamine) beta-mono-oxygenase by cyanide (CN-) and azide (N3-) ions have been investigated by using steady-state methods. Both anions show complex non-competitive-inhibition patterns with respect to ascorbate, suggestive of anion binding at two different sites on the oxidized enzyme. To further investigate this finding, e.p.r. titrations of CN- and N3- binding to the 63Cu-reconstituted enzyme were carried out. Addition of approx. 2 equiv. of CN- to cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…Protein-model complex * The line-width was 4.5, 4.5, 5.0 mT and the line-shape was 40 % Gaussian, 60 % Lorentzian; EPR parameters from [19]. † The line-width is 1.0, 1.0, 6.5 mT and 100 % Gaussian line-shape; the present study.…”
Section: Oxidation Of Pmmo With K 3 Fe(cn) 6 and Addition Of Inhibitorsmentioning
confidence: 64%
See 2 more Smart Citations
“…Protein-model complex * The line-width was 4.5, 4.5, 5.0 mT and the line-shape was 40 % Gaussian, 60 % Lorentzian; EPR parameters from [19]. † The line-width is 1.0, 1.0, 6.5 mT and 100 % Gaussian line-shape; the present study.…”
Section: Oxidation Of Pmmo With K 3 Fe(cn) 6 and Addition Of Inhibitorsmentioning
confidence: 64%
“…The EPR spectrum of DβM shows significant differences upon addition of the inhibitors azide and cyanide [19], whereas the EPR spectrum of the copper site of pMMO is unaffected by these small molecules. Here, we suggest that they do not bind to the EPR visible copper site of pMMO.…”
Section: Epr Investigationmentioning
confidence: 96%
See 1 more Smart Citation
“…After observing that FGE contained ∼1 copper atom/enzyme, we made an effort to remove the metal from the protein to demonstrate its requirement for catalytic activity. Cyanide is known to be an inhibitor of copper-containing oxidases ( 36 38 ). Attempting to extract copper through pretreatment with 5 molar eq of KCN did decrease the activity of Hs -cFGE (but not Sc -FGE) by a modest amount, suggesting that it could gain access to the bound copper ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the catalytic rates of both human and bacterial FGE were significantly increased upon activation with stoichiometric amounts of Cu 2+ , and that turnover was inhibited by the addition of cyanide to FGE reaction mixtures. Previous reports have shown that the inhibition of aerobic copper oxidases by CN − results from ligation of CN − at the metal center (in the reduced state of Cu 1+ ), which prevents oxygen binding and substrate activation ( 38 ). Furthermore, FGE activity was extinguished completely after treating the enzyme with a combination of a chelator and a reductant, reinforcing the highly specific and tight binding interaction between FGE and Cu 2+ .…”
Section: Discussionmentioning
confidence: 99%